Parasite and Cancer Relationship - Çelik, Figen; Şimşek, Sami (Galenos Publishing House, 2022)
Cancer is a life-threatening disease that occurs as a result of the uncontrolled proliferation of cells in any organ or tissue of the body. Parasites are dangerous organisms that can cause death in some cases. Parasite and cancer cells are similar in their capacity to survive and proliferate independently of exogenous growth factors, to be resistant to apoptosis, and to evade host immune mechanisms. Therefore, it is difficult for the body to completely get rid of cancer cells and parasitic agents. In vitro studies or experimental animal studies examining the parasite-cancer relationship have shown that besides parasites that can cause cancer directly, there are also parasites that can indirectly stimulate cancer development through various mechanisms. On the other hand, it is known that the immune response against some parasites can show antitumoral activity in the body. Parasitic agents can have both tumoral and antitumoral effects through regulation of immune response, prevention of metastasis and angiogenesis, inhibition of proliferative signals, and regulation of inflammatory responses that induce cancer development. © 2022 Turkish Society for Parasitology.
Parazit ve Kanser İlişkisi
Keywords: antigen; Cancer; drug; parasite